THE ROLE OF THE LIBRARΙΑΝ IN A MODERN INFORMATION SERVICE - NIKTA, MARINA (Qualitative and Quantitative Methods in Libraries; Vol 10 No 4 (2021): December issue 2021, 2022)
In an information environment, where the whole range of information chain is dominated by meeting the needs of customers-users, the offer of well-structured services, whose organization will have a clear orientation to users will be constantly in demand and librarians are well aware of how to meet this requirement. The ability of information experts to evaluate and organize printed and electronic information sources proves to be a particularly useful skill as it offers them another advantage over other information professionals.